Conceptualising the lessons-learned process in project management: Towards a triple-loop learning framework. Issue 7 (October 2017) - McClory, Sue; Read, Martin; Labib, Ashraf
Abstract: In order to improve success rates of project management, this conceptual paper proposes the inclusion of knowledge management and organisational learning through projects as core aspects of the process, from both individual and organisational perspectives. The lessons-learned process within the project management profession is scrutinised in an attempt to provide new models to overcome the difficulties that inhibit success. Empirical research data from 66 practitioners in an online qualitative survey have influenced the development of our conceptual model. We review single- and double-loop learning systems within the organisation environment, and develop a triple-loop of learning for projects that forms the basis of a new framework. This research will enable future development of processes for utilising the lessons-learned throughout the project life-cycle and the organisation. Graphical abstract: Highlights: BoKs and handbooks provide little detail on the lessons-learned process. Few organisations identify and capture relevant lessons, and fewer utilise them. Projects need knowledge management and organisational learning aspects. A culture of learning throughout a project should be part of benefits management. Triple-loop learning provides organisational structure to improve lessons-learned.